2022
DOI: 10.1063/5.0088036
|View full text |Cite
|
Sign up to set email alerts
|

Vibrations of wind turbine blades in standstill: Mapping the influence of the inflow angles

Abstract: The present investigation used numerical simulations to study the vibrations of a wind turbine blade in standstill. Such vibrations are presumed to affect horizontal axis wind turbine designs and can jeopardize the structural integrity of the machine. The applied numerical methods relied on a fluid–structure interaction (FSI) approach, coupling a computational fluid dynamics (CFD) solver with a multibody finite-element structural solver. A 96-m-long wind turbine blade was studied for a large parametric space, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 48 publications
5
21
0
Order By: Relevance
“…5. From earlier work (Horcas et al, 2022;Riva et al, 2022), it is known that, for the low wind speeds experienced here, the structural mode shape obtained in HAWCSTAB2 is very similar to the deflection shape seen in FSI.…”
Section: Forced-motion Simulationssupporting
confidence: 78%
See 1 more Smart Citation
“…5. From earlier work (Horcas et al, 2022;Riva et al, 2022), it is known that, for the low wind speeds experienced here, the structural mode shape obtained in HAWCSTAB2 is very similar to the deflection shape seen in FSI.…”
Section: Forced-motion Simulationssupporting
confidence: 78%
“…As the computations presented here are computationally heavy, three flow scenarios are picked with basis in the study of Horcas et al (2022). One case which shows high vibrations in the mapping study of Horcas et al (2022) is the P = 100 • , I = 50 • case.…”
Section: Cases Studiedmentioning
confidence: 99%
“…9 shows the results for the flow case P100-I50. The spanwise power per cycle P cycle is here found as the injected work averaged over the time span of n cycles as presented in Horcas et al (2022). The work w s over n cycles is found as the integration over the time range of the sectional loads F s and the velocity of the considered section us .…”
Section: Resultsmentioning
confidence: 99%
“…Originally in the work of Horcas et al (2022), cases P90-I50 and P95-I50 were found to not cause VIVs, as found in the neighbouring case P100-I50. However, from the FM amplitude sweeps depicted in Fig.…”
Section: Multiple-amplitude Cases / Initial Condition Dependenciesmentioning
confidence: 90%
See 1 more Smart Citation